ANALYSIS OF THE CLINICAL CASE OF COMMON CEREBRAL SINUS THROMBOSIS IN AN HIV- INFECTED PREGNANT WOMAN - Зиборова, Светлана Станиславовна; Борзыкин, Сергей Владимирович; Ким, Ирина Олеговна; Букреева, Елена Николаевна; Московкин, Никита Сергеевич; Полукарова, Елена Алексеевна; Пеганова, Марина Анатольевна (Medicine in Kuzbass, 2019)
Subject of research. To study the influence of pathogenic factors and predisposing conditions on the development of cerebral thrombosis.Results. A 37-year-old woman complained of severe headache. The patient was registered for AIDS, received antiretroviral therapy. At the age of 18, the patient suffered from syphilis. Got sick during pregnancy. An example of individual selection of anticoagulant therapy is given.Application. Neurology, diagnosis and treatment of cerebral thrombosis.Summary. The interest of observation is the difficulty of diagnosis and the importance of individual selection of anticoagulant therapy. SCT, MRI and UDS BCA help in diagnosis and allow to trace the dynamics of the process.
Keywords: thrombosis of venous sinuses of the brain; pregnancy; childbirth; HIV